Aplikasi Monitoring Dalam Evaluasi Akademik Untuk Penilaian Kinerja Guru Berbasis Web Menggunakan Metode Behaviorally Anchor Raating Scale (Studi Kasus: SD Negeri Cihuni I) - Ahmad Saprudin; Agung Perdananto (CV. Multi Kreasi Media, 2023)
SD Negeri Cihuni I is an elementary school that was established in Tangerang Regency, Banten. At SD Negeri Cihuni I the teacher performance research process has not yet been carried out with applications that have not been based on the criteria that have been determined by the Minister of National Education. Because of this, the Assessment Team does not yet have consistent rules and it is still difficult to conduct an assessment because they are still following the rules made by the Principal. As a solution to the existing problems, a website-based teacher performance appraisal application was created that can help reduce processing time in the teacher performance assessment process. The teacher performance assessment process in the application will use the Behaviorally Anchor Rating Scale method. The teacher performance assessment that will be carried out will be assessed by the principal and teacher. Based on the results of trials on each function in the system, it shows that the application of teacher performance assessment by applying the Behaviorally Anchor Rating Scale method at SD Negeri Cihuni I has been running well and the results of the calculations are appropriate. In addition, the application can also provide recaps and reports on teacher performance assessments.